2006
DOI: 10.1016/j.crci.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Polymer stabilization: present status and possible future trends

Abstract: Stabilization of polymer material continues to be an important technical field with lot of industrial and scientific attention. Future developments in the field of polymer stabilization need to reflect the corresponding economical requirements. However, ecological requirements start to play increasingly important role in development of stabilization packages for polymers. Present theoretical understanding of polymer degradation and stabilization principles does not yet sufficiently cover the full chemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…If, for any reason, the antioxidant is not injected into the polymer, the product is dark brown after a short time and its physical and mechanical properties are practically altered. The reason for this is the destruction of the polymer by oxidation and the change of nature [9,10]. Even a simple monophosphate antioxidant such as butylated hydroxytoluene (BHT) may also reduce the antioxidant activity and create a quinone system, which can act as a color agent in the polymer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…If, for any reason, the antioxidant is not injected into the polymer, the product is dark brown after a short time and its physical and mechanical properties are practically altered. The reason for this is the destruction of the polymer by oxidation and the change of nature [9,10]. Even a simple monophosphate antioxidant such as butylated hydroxytoluene (BHT) may also reduce the antioxidant activity and create a quinone system, which can act as a color agent in the polymer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of additives can also disturb monomer recovery process. Because of these technical problems which are not favorable from an industrial point of view, in recent years, few investigations have been reported on the use of antioxidants in the polymerization of propylene, and their effect and chemical structures on the activity of catalyst and properties of the final products. Antioxidants are categorized into primary and secondary classes.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme IV shows schematically how a combination of primary and secondary antioxidants functions in a polyolefin matrix [70]. Some metal chelate scavengers may also be based on a tertiary phenolic structure thereby introducing two antioxidant properties into the same molecule.…”
Section: Flame Retardancementioning
confidence: 99%
“…where R'. PO3 is an organophosphite, for example tris(2,4-di-tert-butylphenyl) phosphite or Irgafos 168, Ciba (see Table 6) Scheme IV: Combined stabilizing activity of primary and secondary antioxidants [70].…”
mentioning
confidence: 99%